TINJAUAN YURIDIS TERHADAP HAK ASUH ANAK AKIBAT PERCERAIAN DIKARENAKAN PESELINGKUHAN (Studi Kasus Putusan No.601/Pdt.G/2020/PN.Mdn) - Putri Nabilah; Suparman Suparman; Andi Maysarah (Law Jurnal, 2022)
ABSTRACTIn the event of a divorce both father and mother can be given the same right to care for and educate their children after divorce especially the divorce referred to in Decision No. 601/Pdt.G/2020/PN.Mdn. So that the problem arises, namely how is the legal review related with post-divorce child custody, what are the underlying factors behind the custody of the child falls to the father in the verdict No.601/Pdt.G/2020/PN.Mdn, how are the judges' considerations in doing this decision No.601/Pdt.G/2020/PN.Mdn in deciding child custody rights to the father as a result of divorce.The type of research used in writing this thesis is juridical normative descriptive analysis. Data collection techniques that used is a literature study (Library Research).Legal reviews related to post-divorce child custody are available on the Marriage Law, namely Article 41, Article 45, Article 47, Article 48 and Article 49. Furthermore, it is also found in the Compilation of Islamic Law, through Article 105. What are the factors behind child custody falling to the father in Decision No.601/Pdt.G/2020/PN.Mdn, firstly, the Defendant/Wife committed an affair and was known to have booked a hotel 2 (two) times with his mistress. Second, the Defendant has admitted his actions before the Plaintiff, his family and traditional leaders had an affair. Third, the affair committed by the Defendant shows that: betrayal and irresponsible behavior of the Defendant as the wife and at the same time the mother in marriage, which makes the Plaintiff and Defendant finally agreed to divorce and was judged by the judge to be unworthy custody of their children, caused by the actions of the Defendant who It is feared that it will have a negative impact on their children.Keywords : Juridical Review, Child Custody, Divorce